2014
DOI: 10.1186/preaccept-1744854612129169
|View full text |Cite
|
Sign up to set email alerts
|

IMP3 as a cytoplasmic biomarker for early serous tubal carcinogenesis

Abstract: Background: Serous tubal intraepithelial carcinoma (STIC) and the p53 signature in tubal mucosa have been supported to be precursor lesions in high-grade serous carcinoma (HGSC) of the fallopian tube, ovary, and peritoneum. It remains critical to find biomarkers for precursor lesions in order to detect HGSCs efficiently. IMP3 is an oncoprotein that has been explored in human malignancies. No studies have specifically addressed the expression of IMP3 in precursor or early lesions of HGSC. The main purposes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The explanation for such a wide range of IMP3 expression in the various studies is not clear but could be related to the different cut-offs for positivity used. Two studies used 10% of positive tumor cells as a cut off [8,26], while the remaining studies used different scoring systems, mostly taking into account staining intensity as well as percentage of positive tumor cells [24,27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for such a wide range of IMP3 expression in the various studies is not clear but could be related to the different cut-offs for positivity used. Two studies used 10% of positive tumor cells as a cut off [8,26], while the remaining studies used different scoring systems, mostly taking into account staining intensity as well as percentage of positive tumor cells [24,27,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of IMP3 is observed in a series of human malignancies, including ovarian, endometrial, and cervical cancers [ 26 28 ]. Our prior study showed that IMP3 may serve as a complimentary biomarker in diagnosing STIC and overexpression of IMP3 in tubal epithelia increases the risk of ovarian serous cancer development [ 29 , 30 ]. It will be of great interest to examine if tubal cytology in combination with biomarker studies may increase the sensitivity and specificity of detecting serous cancer of tubal origin.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the overexpression of IMP3 which is normally not expressed in normal adult tissue may be involved in the initial process of tubal or pelvic serous carcinogenesis and IMP3 signature may serve as a hidden preneoplastic biomarker for these tumors in women. [11] SCOUTs forming a morphologically distinct stretch of the secretory cell population have been linked to serous neoplasia and serve as a biomarker. [12] STICs called also as tubal lesions in transition are noninvasive carcinomas recognized in the fallopian tube.…”
Section: Introductionmentioning
confidence: 99%